2019
DOI: 10.3390/atmos10080436
|View full text |Cite
|
Sign up to set email alerts
|

Observed Trends in Thermal Stress at European Cities with Different Background Climates

Abstract: Intensification of extreme temperatures combined with other socioeconomic factors may exacerbate human thermal risk. The disastrous impacts of extreme weather during the last two decades demonstrated the increased vulnerability of populations even in developed countries from Europe, which are expected to efficiently manage adverse weather. The study aims to assess trends in the exposure of European populations to extreme weather using updated historical climatic data in large European cities of different local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 59 publications
(88 reference statements)
0
20
0
1
Order By: Relevance
“…These findings for Athens are similar with the results reported in other Mediterranean or eastern Europe cities. For instance, a significant increase in both the number of HW days and the number of long HWs have been recently reported in Madrid, Palma, Nicosia, Rome, Sofia, Zagreb and Ljubljana [19,61,62].…”
Section: Discussionmentioning
confidence: 98%
“…These findings for Athens are similar with the results reported in other Mediterranean or eastern Europe cities. For instance, a significant increase in both the number of HW days and the number of long HWs have been recently reported in Madrid, Palma, Nicosia, Rome, Sofia, Zagreb and Ljubljana [19,61,62].…”
Section: Discussionmentioning
confidence: 98%
“…The more than 23% growth in Alaska's population mainly increased the outskirts of the three major cities (Anchorage, Fairbanks, Juneau). Recent studies showed that increasing urbanization and improved urban planning, among other things, altered the thermal stress in European cities of different background climates over time [53]. Given the few urban sites in Alaska, of which many have only short time series, the assessment of small-scale differences in thermal comfort and planning for its improvement remain a challenge.…”
Section: Discussion Conclusion and Outlookmentioning
confidence: 99%
“…E-OBS also allows grid box average comparisons with the results of Regional Climate Models for validation purposes [25][26][27]. These datasets were used in various urban climatology studies relying on observations addressing the challenges of climate change in European cities, e.g., assessment of the impact of climate change on thermal performance of residential buildings [28]; and change in extreme heat/cold stress [29][30][31].…”
Section: In Situ Meteorological Datamentioning
confidence: 99%